DOI: 10.11606/t.42.2007.tde-18102007-123826
|View full text |Cite
|
Sign up to set email alerts
|

Deficiências concomitantes da proteína reguladora Fator H e do componente C9 do complemento.

Abstract: Agradecimentos À Dra. Lourdes Isaac. Os anos ainda por vir da minha vida serão insuficientes para te retribuir tanta confiança, tanta dedicação, tanto apoio, a fim de que este grande dia chegasse. Muito mais do que orientadora e profissional exemplar você foi companheira, mãe e amiga. Nos momentos mais difíceis você sempre esteve lá, sempre! Lou, muito obrigada por tanto, tanto, tanto... Ao Dr. Shaker Chuck Farah do Departamento de Bioquímica da USP por ser sempre alguém com quem pudemos contar em tantas dific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 82 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…24 The present work demonstrates some of these trends, such as the increase in dimensionality from compound 14 to compound 17 (2D to 3D), which arises from heating an identical combination of metal and ligands for 6 days as opposed to 20 h. However, since the synthesis conditions are largely identical for the crystallization of all 20 structures, the most striking pattern evident here is that the presence of fluorine rather than hydrogen in an aromatic ring favors the formation of framework structures with higher dimensionalities, providing another tool whereby structures of a particular type can be targeted in synthesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 The present work demonstrates some of these trends, such as the increase in dimensionality from compound 14 to compound 17 (2D to 3D), which arises from heating an identical combination of metal and ligands for 6 days as opposed to 20 h. However, since the synthesis conditions are largely identical for the crystallization of all 20 structures, the most striking pattern evident here is that the presence of fluorine rather than hydrogen in an aromatic ring favors the formation of framework structures with higher dimensionalities, providing another tool whereby structures of a particular type can be targeted in synthesis.…”
mentioning
confidence: 99%
“…We have previously shown that the dimensionalities of metal dicarboxylate frameworks can be influenced by a range of factors, including reaction temperature, 18 pH and time, 19 ligand flexibility, 20 the use of chiral versus racemic ligands, 21 the disposition of the carboxylate groups around a ring, 22,23 and the size of the metallic cation. 24 The present work demonstrates some of these trends, such as the increase in dimensionality from compound 14 to compound 17 (2D to 3D), which arises from heating an identical combination of metal and ligands for 6 days as opposed to 20 h. However, since the synthesis conditions are largely identical for the crystallization of all 20 structures, the most striking pattern evident here is that the presence of fluorine rather than hydrogen in an aromatic ring favors the formation of framework structures with higher dimensionalities, providing another tool whereby structures of a particular type can be targeted in synthesis. Supporting Information Available: Crystallographic files in CIF format, complete descriptions of synthesis conditions, details of structure solution, extensive structure descriptions, and thermogravimetric analysis data.…”
mentioning
confidence: 99%